Effectiveness of Water-Based Exercise/Aquatic Exercise for Individuals with Low Back Pain: a Literature Review - Selandani, Ajeng Adela; Rusmanto, Salma Anas; Hana, Azzahra Putri Callista; Karimah, Dzakiya Diena; Ramadhani, Jihan Nabila; Octafiani, Afinda Krisdeana; Pristianto, Arif (UNUSA Press, 2025)
Background: Low back pain (LBP) is a common complaint that affects many individuals and can significantly reduce quality of life. Water-based exercise has been proposed as an effective therapeutic method to reduce pain and improve physical function in patients with LBP. Methods: A literature review was conducted by searching for relevant studies in reputable medical databases. Inclusion criteria included studies that compared water-based exercise with land exercise in individuals with LBP. Results: Studies show that both water-based exercise and land exercise are effective in reducing low back pain. However, water-based exercise tends to overestimate its effect due to publication bias. Nonetheless, water-based exercise provided a significant reduction in VAS scores. Land exercise showed additional benefits with significant improvements in emotional role and physical function on the SF-36, as well as a decrease in the ODI. Conclusion: Based on a literature review of seven selected articles, waterbased exercises have been shown to be effective in reducing pain in cases of low back pain (LBP). However, its application must consider the technical conditions and medical history of the patient.